Blended Learning Method in Korean Final Consonant Pronunciation Learning for Beginner Indonesian KFL Learners - Azizah, Asma; Ansas, Velayeti Nurfitriana (Universitas 17 Agustus 1945 Surabaya, 2025)
The difference between the writing and pronunciation of the final consonants in Korean language has been considered as one of the causes that makes students learning Korean as a foreign language (KFL) find it difficult to pronounce Korean words correctly. This descriptive qualitative study aimed to investigate the beginner students’ pronunciation of the final consonants in Korean. Data were collected from 15 students of the Korean Language Education Department, FPBS, UPI, who were asked to pronounce 10 Korean words with final consonants. PRAAT application was used to analyze pronunciation errors. The results show that the percentage of final consonant error pronunciation is 37%. Based on the analysis, participanting students who have high GPA, knowledge of pronunciation theory, and Indonesian as a native language pronounced final consonants better. The data also shows that students’ knowledge of vocabulary was not always linear with pronunciation realization. It depended on the phonological and morphological environments of the vocabulary. These analysis results were then used to inform the design of our flipped classroom model for the implementation of blended learning on Korean final consonant pronunciation.